use the factor theorem tho determine whether g(x)=x+1 is a factor of f(x)=5x3+x2-5x-1
Answers
Answered by
3
Step-by-step explanation:
g(x) = x+1
then, g(x) = 0
so, x+1 = 0
x = -1
now f(x) = 5x³+x²-5x-1
f(x) = 0
now, f(-1) = 5(-1)³+(-1)²-5(-1)-1
f(-1) = -5+1+5-1
f(-1) = 0
therefore the condition g(x) = x+1 is satisfying the equation and g(x) = x+1 is a factor of f(x) = 5x³+x²-5x-1.
pls mark as brainliest
Answered by
2
Answer:
g(x)=x+1
g(x)=x+1=0
g(x)=x=_1
f(_1)=5(_1)cube+(_1)^_5(_1)_1
f(_1)=_5+1+5_1
f(_1)=0
Similar questions